In situ hybridisation of albumin mRNA in normal liver and hepatocellular carcinoma with a digoxigenin labelled oligonucleotide probe. - Murray, G I (1992)
AIMS: To study the localisation and distribution of albumin mRNA in normal liver and hepatocellular carcinoma by in situ hybridisation with an oligonucleotide probe. METHODS: A 51 base oligonucleotide was synthesised from a sequence at the 5' end of the human albumin gene and the probe was labelled at its 3' end with digoxigenin 11-dUTP. Formalin fixed, wax embedded sections of liver biopsy specimens were used to study the localisation and distribution of albumin mRNA. After in situ hybridisation the bound probe was visualised using a digoxigenin antibody conjugated with alkaline phosphatase. RESULTS: In normal liver albumin mRNA was detected in hepatocytes and no positive signal was observed in biliary epithelium, vascular endothelium, or Kupffer cells. In 75% (9/12) of the hepatocellular carcinomas studied a positive hybridisation signal was observed in tumour cells. CONCLUSIONS: Albumin mRNA can be detected in sections of formalin fixed, wax embedded liver, a digoxigenin labelled probe is ideally suited for in situ hybridisation of liver because there is no background from the detection system. The identification of albumin mRNA may be a useful marker of hepatocellular carcinoma, and the demonstration of albumin mRNA by in situ hybridisation overcomes the potential background problem associated with albumin immunohistochemistry.